The Recombinant Form of Trypanosoma cruzi P21 Controls Infection by Modulating Host Immune Response - Martins, Flávia Alves; dos Santos, Marlus Alves; Santos, Júlia de Gouveia; da Silva, Aline Alves; Borges, Bruna Cristina; da Costa, Mylla Spirandelli; Tavares, Paula Cristina Brígido; Teixeira, Samuel Cota; Brígido, Rebecca Tavares e Silva; Teixeira, Thaise Lara; Rodrigues, Cassiano Costa; Silva, Nadjania Saraiva de Lira; et al. (Frontiers in Immunology, 2020)
Trypanosoma cruzi P21 protein (P21) is a putative secreted and immunomodulatory molecule with potent bioactive properties such as induction of phagocytosis and actin cytoskeleton polymerization. Despite the bioactive properties described so far, the action of P21 on parasite replication in muscle cell lineage model or T. cruzi parasitism during acute experimental infection is unclear, and here it was proposed to clarify this. We observed that recombinant P21 (rP21) decreased the multiplication of T. cruzi in C2C12 myoblasts, phenomenon associated with greater actin polymerization and IFN-γ and IL-4 higher expression. During experimental infection, lower cardiac nests, inflammatory infiltrate and fibrosis were observed in mice infected and rP21 treated. These results were correlated with large expression of IFN-γ counterbalanced by high levels of IL-10, which was consistent with the lower cardiac tissue injury found in these mice. We have also observed that upon stress, such as the presence of the IFN-γ cytokine, T. cruzi produced more P21. The effect of P21 in controlling the replication of T. cruzi, may indicate an evolutionary mechanism of survival developed by the parasite. Thus, when subjected to different stress conditions, the protozoan produces more P21, which induces T. cruzi latency in the host organism, enabling the protozoan to evade the host's immune system.